PERAN GURU DALAM INTERNALISASI NILAI-NILAI MULTIKULTURAL SISWA DI SMP NEGERI 1 NAMORAMBE - Dyna MT Pasaribu; Fazli Rachman; Ramsul Nababan; Sampitmo Habeahaan; Sri Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of teachers in internalizing multicultural values ​​to students and teacher strategies in overcoming obstacles encountered during the learning process and school activities at SMP Negeri 1 Namorambe. The background of this study is based on the highly pluralistic conditions of Indonesian society, which have the potential to trigger cultural and value clashes if not managed through appropriate multicultural education. The research method used is descriptive qualitative with a field approach. The research subjects consisted of teachers at SMP Negeri 1 Namorambe, especially Pancasila and Citizenship Education teachers. Data were collected through participatory observation techniques, in-depth interviews, and documentation. The data analysis technique follows the Miles and Huberman model which includes three stages: data reduction, data presentation, and conclusion drawing and verification. The focus of value internalization in this study includes aspects of pluralism (mutual respect), democracy (equality of rights and obligations), and humanism (human dignity). The internalization process is reviewed through three main stages: the value transformation stage, the value transaction stage, and the transinternalization stage. The research results show that teachers at SMP Negeri 1 Namorambe have optimally internalized multicultural values ​​through learning channels, school activities, and the formation of an inclusive culture. Teachers have successfully carried out four key roles: as professional educators who ensure equality, creative learning agents based on digital media, superior human resources who are adaptive in guiding students persuasively, and real role models in acting fairly without discrimination of religion and ethnicity. Keywords: Teacher, Values, Multiculural.